Reshoring as a Modern Trend in the Development of the Global Economic System - Oksana A. SAGINА1; Sergey V. PONOMAREV2; Aminat M. MUSAYEVA3; Seyidullakh G. KHANMAGOMEDOV3; Evgeniya K. KARPUNINA4 (Communications of International Proceedings, 2020)
The purpose of the research is to reveal the economic essence of reshoring, and analyse the impact of reshoring on the effectiveness of economic systems in the world. Methods of economic analysis were used to study the influence of reshoring on the effectiveness of economic systems. The analysis and subsequent cross-country comparison were carried out in two periods: 1999-2007 and 2010-2018. The following indicators were used in the analysis: GDP growth; the share of industry in the GDP structure; the share of services in the GDP structure; the current account balance. It is revealed that currently reshoring is not an effective tool for overcoming turbulence in the world economy. The analysis of reshoring policy showed that: 1) its local performance in terms of increasing the share of manufacturing in GDP; 2) the process of restoring does not change the growth trend of "service economy" in most countries; 3) the weakness of the current reshoring to improve the balance of payments. It is justified that an increase in the flexibility of the reshoring policy in terms of taxes, regulations, effective personnel policy, and tariff reduction will help diffuse the weaknesses of reshoring and attract direct foreign investment, as well as create conditions for making the most of reshoring in developing sound competition and countering global crises.
Keywords: Reshoring; Offshoring; Industrialisation; Deindustrialisation; Sustainability; Economic Security.